2000
DOI: 10.1111/1469-8986.3730361
|View full text |Cite
|
Sign up to set email alerts
|

Phasic heart period reactions to cued threat and nonthreat stimuli in generalized anxiety disorder

Abstract: The hallmark of generalized anxiety disorder (GAD) is chronic uncontrollable worry. A preattentive bias toward threat cues and hypervigilance may support this ongoing state of apprehension. A study was conducted to bridge the attentional and physiological underpinnings of GAD by examining phasic heart period (HP) responses to cued threat and nonthreat stimuli. Thirty-three GAD clients and 33 nonanxious control participants engaged in an S1-S2 procedure that employed cued threat and nonthreat word stimuli, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 12 publications
5
74
0
1
Order By: Relevance
“…The study by Thayer et al (2000) mentioned in the introduction used a higher-order conditioning procedure. An earlier study by Pitman and Orr (1986) found no differences in differential conditioning during acquisition between GAD patients (as defined by DSM-III criteria) and controls, but comparison with this study is difficult given the changes in GAD criteria from DSM-III-R onwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Thayer et al (2000) mentioned in the introduction used a higher-order conditioning procedure. An earlier study by Pitman and Orr (1986) found no differences in differential conditioning during acquisition between GAD patients (as defined by DSM-III criteria) and controls, but comparison with this study is difficult given the changes in GAD criteria from DSM-III-R onwards.…”
Section: Discussionmentioning
confidence: 99%
“…These processes include acquisition, within-session extinction, extinction recall, conditioned inhibition and conditioned fear-generalization. For example, an enhanced fear acquisition may be characteristic of social phobia (Lissek et al, 2008a), generalized anxiety disorder (GAD; Thayer, Friedman, Borkovec, Johnsen, & Molina, 2000), or post-traumatic stress disorder (PTSD; Orr et al, 2000;Peri, Ben-Shakhar, Orr, & Shalev, 2000). Impaired within-session fear extinction has been shown for individuals with panic disorder (PD; Michael, Blechert, Vriends, Margraf, & Wilhelm, 2007;Otto et al, 2014) or GAD (Pitman & Orr, 1986), whereas impaired extinction recall could be present in PTSD (Milad et al, 2008) or obsessive-compulsive disorder (OCD; Milad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has found that vagal influence as indexed with RSA tended to override sympathetic influence in predicting heart rate (e.g., Uytdehaage and Thayer, 1989). In another study, researchers measured orienting and defensive cardiac patterns in a conditioning paradigm (Thayer, Friedman, Borkovec, Johnsen, & Molina, 2000). The results showed that people with lower RSA (who were also diagnosed with general anxiety disorder) showed persistent defensive responses to threatening words that high RSA people responded to only with orienting.…”
Section: Empirical Support In Humansmentioning
confidence: 99%
“…Çarpıntı yakınmasının en sık görüldüğü psikiyatrik hastalık panik bozukluktur (14 (19). Fobik bozukluk hastalarına korkulan nesne gösterildiğinde kalp atım hızında belirgin artış olduğu tespit edilmiştir (20).…”
Section: Kaygı Bozukluklarıunclassified